Instantaneous Top-of-Atmosphere Albedo Comparison between CERES and MISR over the Arctic - Yizhe Zhan (Remote Sensing, 2018)
The top-of-atmosphere (TOA) albedo is one of the key parameters in determining the Arctic radiation budget, with continued validation of its retrieval accuracy still required. Based on three years (2007, 2015, 2016) of summertime (May⁻September) observations from the Clouds and the Earth’s Radiant Energy System (CERES) and the Multi-angle Imaging SpectroRadiometer (MISR), collocated instantaneous albedos for overcast ocean and snow/ice scenes were compared within the Arctic. For samples where both instruments classified the scene as overcast, the relative root-mean-square (RMS) difference between the sample albedos grew as the solar zenith angle (SZA) increased. The RMS differences that were purely due to differential Bidirectional Reflectance Factor (BRF) anisotropic corrections ( <semantics> σ A D M </semantics> ) were estimated to be less than 4% for overcast ocean and overcast snow/ice when the SZA ≤ 70°. The significant agreement between the CERES and MISR strongly increased our confidence in using the instruments overcast cloud albedos in Arctic studies. Nevertheless, there was less agreement in the cloud albedos for larger solar zenith angles, where the RMS differences of <semantics> σ A D M </semantics> reached 13.5% for overcast ocean scenes when the SZA > 80°. Additionally, inconsistencies between the CERES and MISR scene identifications were examined, resulting in an overall recommendation for improvements to the MISR snow/ice mask and a rework of the MISR Albedo Cloud Designation (ACD) field by incorporating known strengths of the standard MISR cloud masks.